Intersex, Hermaphroditism, and Gonadal Plasticity in Vertebrates: Evolution of the Mullerian Duct and Amh/Amhr2 Signaling - Adolfi, Mateus Contar; Nakajima, Rafael Takahiro [UNESP]; Nobrega, Rafael Henrique [UNESP]; Schartl, Manfred; Lewin, H. A.; Roberts, R. M. (Annual Reviews, 2019)
In vertebrates, sex organs are generally specialized to perform a male or female reproductive role. Acquisition of the Mullerian duct, which gives rise to the oviduct, together with emergence of the Amh/Amhr2 system favored evolution of viviparity in jawed vertebrates. Species with high sex-specific reproductive adaptations have less potential to sex reverse, making intersex a nonfunctional condition. Teleosts, the only vertebrate group in which hermaphroditism evolved as a natural reproductive strategy, lost the Mullerian duct during evolution. They developed for gamete release complete independence from the urinary system, creating optimal anatomic and developmental preconditions for physiological sex change. The common and probably ancestral role of Amh is related to survival and proliferation of germ cells in early and adult gonads of both sexes rather than induction of Mullerian duct regression. The relationship between germ cell maintenance and sex differentiation is most evident in species in which Amh became the master male sex-determining gene.
Keywords: hermaphroditism; intersex; Amh; Mullerian duct; evolution; vertebrates